The sustainability of agricultural trade: The case of South Africa - Thomas van Huyssteen; Djiby Thiam; Sanderine Nonhebel (Cleaner Production Letters)
Trade in agricultural products will be a crucial component of adaptive responses to global food insecurity and ensuring its sustainability is thus crucial. This is particularly important for resource scarce countries because agricultural trade allows for the virtual transfer of the resources required for production. This is important because agricultural production has significant resource requirements as well as substantial environmental, climatic and economic impacts. Assessing the sustainability of agricultural trade has proven to be a complex challenge due to a lack of frameworks available to comprehensively assess it and the ‘silo approach’ to resource management. To combat these problems new frameworks and analysis techniques which account for numerous sectors and impacts need to be developed. The objective of this paper was to provide and utilise such a framework to assess the sustainability of agricultural trade. To do this, the Water-Energy-Food Land-Economy-Climate framework was proposed. The framework was used in combination with a lifecycle analysis approach to assess the sustainability of agricultural trade in South Africa. Despite exporting 25% more agricultural products than they imported, the results showed that the production of South Africa's agricultural imports required 65% more water, 3% more energy, and 44% more land than exports. Further, imports generated 98% more CO₂ and 103% more PO4 emissions than exports. Finally, South Africa was shown to generate 64% more economic value from their agricultural exports than their imports cost. Overall, the results show that according to the Water-Energy-Food Land-Economy-Climate framework used, and accounting for the South African resource context, the country had a sustainable agricultural trade mix.